Environmental compliance and business strategies practices of entrepreneurial ventures - Stupnytskyi Viktor; Filipishyna Liliya; Chumak Oksana; Gonchar Viktoriya; Komandrovska Veronika; Iefimova Ganna (E3S Web of Conferences, 2023)
The study is devoted to the research of environmental compliance and business strategies of the practice of venture enterprises. The purpose of the study is to determine the role of environmental compliance in the business strategies of enterprises and to reveal the potential of a positive impact on sustainable development. The paper examines hypotheses regarding the favourable impact of environmental compliance on the competitiveness and innovative potential of enterprises. Environmental compliance and business strategies of enterprises have the potential to promote sustainable environmental development, which is currently only 10% used. This requires the active participation of enterprises in the implementation of environmental practices, investments in innovative solutions and the development of knowledge. The study highlights the need to support and promote practices such as venture entrepreneurship, which contribute to the creation of new environmentally relevant technologies, products and services. Therefore, the results of this work indicate the importance of developing and implementing ecologically appropriate business strategies in business practices. This can contribute to improving the environmental condition, ensuring sustainable development and strengthening the competitive positions of national economies.